The Concept of Pawnbroking (Rahn) in Sharia Financial Institutions - Valentino, Gian Nadhif; Husnayan, Husain Althaf; Rozik, Abidur; Dwiky Maulana, Dissy Farrel; Firmansyah, Ahmad Ardi; Ramadhani, Catur Wahyu; Kurniawan, Taufiq (SYARIAH : Jurnal Ilmu Hukum, 2025)
In muamalah, Islam also recognises pawnbroking, or rahn. A rahn contract is a debt agreement between the rahin (borrower/pawnbroker) and the murtahin (pawnbroker/lender), who’s someone who pawns their goods as collateral for their debt. To meet economic needs, people sometimes face many difficulties, and various methods can be used to ensure that their needs are still met. For example, by pawning valuable items such as gold, land, and others. There are various views among Islamic scholars in discussing rahn. In general, pawnbroking is permitted under certain terms and conditions. Islamic pawnbroking (rahn) with standard rules still faces many problems, such as legal norms in rahn. Therefore, it’s also necessary to discuss the norms in rahn activities that are expected to be in accordance with Islamic law. In terms of collateral (rahin), this is a legal issue that also needs to be discussed in the concept of pawnbroking. There has been a paradigm shift in pawnbroking in Islamic legal and economic terminology to debt. In addition, this article aims to explain the concept of rahn, law, and other matters related to rahn (pawnbroking) so that the public can better understand pawnbroking and the concept of pawnbroking that’s justified according to Islam.